Penggunaan Adverbia Pada Naskah Pidato Presiden Joko Widodo Dalam Sidang MPR-DPR-RI 2021 - Nahda Nadila (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Adverbs are adverbs or commonly referred to as additional adverbs. Adverbs are divided into several types, namely adverbs in terms of form, adverbs in terms of semantics, adverbs in terms of syntactic behavior, conjunctive adverbs, discourse opening adverbs, and adverbs of other word classes. In this study it refers more to the application of adverbs in terms of form and adverbs in terms of their semantic behavior in speech texts. The data is sourced from social media. The research method used in this study is a qualitative descriptive approach method.